Characterization of packaging ability to protect beer from light degradation and introduction of a new Packaging Riboflavin Index - Petr Gabriel; Miroslav Dienstbier; Karel Fous; Dagmar Matoulková (Kvasný průmysl, 2022)
Bottled beer is exposed to light during transport or storage, which can unfavourably affect its sensory properties. One of the functions of the packaging is to provide maximum protection against possible light degradation. Riboflavin (vitamin B2), which acts as a photosensitizer, is a key substance for the occurrence of light degradation in beer. Riboflavin absorbs light in the visible region of the spectrum and transfers its energy to other compounds. A cascade of subsequent chemical reactions leads to sensory damage to the beer. Based on the transmission spectrum of packaging (glass and plastic), the Packaging Riboflavin Index (PRFI)was introduced. PRFI was designed as a tool which quantitatively assesses the ability of packaging to protect beer from light damage. The basic types of commercially used glass and plastic packaging were compared using this index. The validity of the index was verified in an experiment with defined light damage of beer in different packaging.